SISTEM LAMPU OTOMATIS BERBASIS IOT DENGAN SENSOR GERAK TUBUH - Mohammad Baharudin Yusuf; Fakhri Rifqi Fahreza; M. Subhakti A. Maulana; Susilawati (PT. Hasba Edukasi Mandiri, 2025)
The development of Internet of Things (IoT) technology enables electronic devices to be controlled automatically and remotely. One of its applications is an automatic lighting system that regulates lamp activation based on the presence of an object. In this study, an IoT-based automatic lamp system was designed using an infrared sensor (IR Obstacle Avoidance) as a motion detector and an ESP32 as the main controller connected to an MQTT broker. Sensor data are sent to the HiveMQ broker and displayed through the MQTT Dash application on a smartphone. The test results show that the system can automatically turn on the lamp when the sensor detects an object and provide real-time feedback through MQTT. The implementation of this system can save energy and improve lighting control efficiency in home and office environments.